United States Strategy Change: From Build Back Better World (B3W) To Partnership For Global Infrastructure And Investment (PGII) - Izza, Atina (Universitas Tribhuwana Tunggadewi, 2025)
In June 2021, U.S. President Joe Biden and G7 leaders launched the Build Back Better World (B3W) initiative – an ambitious global infrastructure partnership grounded in democratic values, transparency, and high standards. B3W was seen as a response to China’s Belt and Road Initiative (BRI), aimed at expanding its influence across developing countries. However, a year later, the United States and G7 nations introduced a new strategy known as the Partnership for Global Infrastructure and Investment (PGII), marking a significant shift in their approach. This study employs a qualitative research method based on discourse analysis to examine this strategic transformation. The findings indicate that the shift from B3W to PGII was driven not only by geopolitical considerations but also by domestic political dynamics in the United States, particularly resistance in Congress. Internal political pressure prompted the Biden administration to adopt a more pragmatic and realistic approach. Accordingly, this study highlights how the interplay between domestic factors and great power rivalry has shaped U.S. foreign policy directions in responding to China’s influence through the BRI. Pada Juni 2021, Presiden AS Joe Biden dan para pemimpin G7 meluncurkan inisiatif infrastruktur global baru yang ambisius: Bangun Kembali Dunia yang Lebih Baik (B3W), sebuah kemitraan infrastruktur yang didorong oleh nilai-nilai, berstandar tinggi, dan transparan. B3W dipandang sebagai respons terhadap Belt and Road Initiative (BRI) yang diusung Tiongkok untuk memperluas pengaruhnya di negara-negara berkembang. Namun, setahun kemudian, Amerika Serikat dan negara-negara G7 memperkenalkan strategi baru bernama Kemitraan untuk Infrastruktur dan Investasi Global (PGII), menandai perubahan signifikan dalam pendekatan mereka. Studi ini menggunakan pendekatan kualitatif berbasis analisis wacana untuk menelaah dinamika tersebut. Hasil analisis menunjukkan bahwa pergeseran dari B3W ke PGII tidak hanya dipengaruhi oleh konteks geopolitik, tetapi juga oleh dinamika politik domestik di Amerika Serikat, terutama resistensi dari Kongres. Tekanan politik internal mendorong pemerintahan Biden untuk mengadopsi pendekatan yang lebih pragmatis dan realistis. Dengan demikian, studi ini menyoroti bagaimana interaksi antara faktor domestik dan rivalitas kekuatan besar membentuk arah kebijakan luar negeri AS dalan merespons pengaruh Tiongkok melalui BRI.